Factors affecting brand loyalty of undergraduates. - Fok, Kah Wai. (2008)
This study aims to identify factors that may have an influence on brand loyalty among undergraduates. Undergraduates were chosen for this study due to their greater spending power. Three types of factors were identified -- product attributes, store attributes and customer characteristics. A sample of 200 undergraduates were chosen and made to undergo a questionnaire survey and frequency tables are used to analyse the data further.